Reduction of graphene oxide by 100 MeV Au ion irradiation and its application as H2O2 sensor - Hareesh, K.; Joshi, R. P.; Shateesh, B.; Asokan, K.; Kanjilal, D.; Late, Dattatray J.; Dahiwale, S. S.; Bhoraskar, Vasant N.; Haram, Santosh K.; Dhole, Sanjay D. (Journal of Physics D-Applied Physics, 2015)
Graphene oxide (GO) synthesized from a modified Hummer's method was reduced (referred, rGO) by using 100 MeV Au ion species and its response to the sense H2O2 was investigated. The changes in the atomic composition and structural properties of rGO after irradiation were studied using x-ray diffraction, Fourier transform infrared spectroscopy and x-ray photoelectron spectroscopy. These results suggested that the removal of the oxygen-containing functional groups and the improvement of the electrochemical performance of reduced graphene oxide (rGO) after ion irradiation. Raman spectroscopic results revealed the increase in the disorder parameter (I-D/I-G) after Au ion irradiation and also the formation of a large number of small sp(2) domains due to the electronic energy loss of ion beam. The resultant rGO was investigated for H2O2 sensing using electrochemical techniques and it showed a good response.
Keywords: electronic energy loss; GO; ion beam irradiation; reduction